Progress in environmental gentrification research and hotspot analysis based on CiteSpace analysis - Yu Pei; Sun Peng (E3S Web of Conferences, 2021)
With the advent of the post-industrial era, environmental improvements and sustainable initiatives that lack sufficient attention to the social justice aspects of environmental changes generates environmental gentrification. The purpose of this paper is to systematically explore the frontiers of gentrification research and the knowledge base of environmental gentrification. Therefore, based on Web of Science Core Collection Database, this paper analysed the progress and hotpots of environmental gentrification using CiteSpace, identified keywords relevant to environmental gentrification and their frequency of co-occurrence using the function of keyword co-occurrence analysis, recognized top ten clusters using the function of cluster analysis. Environmental gentrification is the frontier on gentrification research, which knowledge base and hotpots research should arouse our attention. This paper can help readers to understand the status quo and development trend of environmental gentrification better, recognize defect in the development of environmental gentrification, and provide a promising direction for future research.